2017
DOI: 10.1152/ajpcell.00222.2016
|View full text |Cite
|
Sign up to set email alerts
|

ATF6 knockdown decreases apoptosis, arrests the S phase of the cell cycle, and increases steroid hormone production in mouse granulosa cells

Abstract: Activating transcription factor 6 (ATF6), a sensor protein located in the endoplasmic reticulum (ER) membrane, is an important factor in the ER stress signaling pathway. ER stress is known to be involved in folliculogenesis, follicular growth, and ovulation; however, the physiological function of ATF6 in mouse granulosa cells remains largely unknown. The aim of this study was to assess the role of ATF6 in mouse granulosa cells with respect to apoptosis, the cell cycle, and steroid hormone production, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…CYP19A1, a key enzyme in E2 synthesis, has been reported to play a key role in follicles during atresia. 14,22 Therefore, we analyzed CYP19A1 mRNA and protein levels in mGCs transfected with miR-205 mimics by performing qRT-PCR and Western blot, respectively. Our results showed that miR-205 overexpression significantly decreased CYP19A1 mRNA ( Figure 3B) and protein ( Figure 3C) expression levels in mGCs.…”
Section: Mir-205 Suppressed E2 Synthesis In Mgcsmentioning
confidence: 99%
“…CYP19A1, a key enzyme in E2 synthesis, has been reported to play a key role in follicles during atresia. 14,22 Therefore, we analyzed CYP19A1 mRNA and protein levels in mGCs transfected with miR-205 mimics by performing qRT-PCR and Western blot, respectively. Our results showed that miR-205 overexpression significantly decreased CYP19A1 mRNA ( Figure 3B) and protein ( Figure 3C) expression levels in mGCs.…”
Section: Mir-205 Suppressed E2 Synthesis In Mgcsmentioning
confidence: 99%
“…In addition, our previous work also revealed that ER stress regulated follicle atresia in mice and goats. Some important proteins in the ER stress, such as lumen and ATF6 [27,28], also have a role in the physiological function of granulosa cells. For XBP1, we just know its expression in the GCs of growing follicles according to the research of Miyuki et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…CYP19A1, a key enzyme in E2 synthesis, was reportedly to play a key role in during atresia follicles (14,21) Thus, we detected CYP19A1 expression on mRNA and protein levels in mGCs transfected with miR-205 mimics by qRT-PCR and western blot, respectively. Our results showed that overexpression of miR-205 significantly decreased the mRNA ( These results implied that miR-205 can regulate E2 synthesis in mGCs by regulating CYP19A1 expression, leading to mGC apoptosis and follicular atresia.…”
Section: Mir-205 Suppresses E2 Synthesis In Mgcsmentioning
confidence: 89%